PERUBAHAN DAN TREN JUMLAH MAHAR DALAM TRADISI PERNIKAHAN DI INDONESIA (ANALISA HADIS TENTANG MAHAR) - Suryani Suryani (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract : In analyzing changes and trends in the amount of dowry in wedding traditions in Indonesia, it can be concluded that there are several factors that influence these changes. Social, economic, cultural growth and religious influence have a significant role in determining the amount of dowry given in marriage. The increase in people's purchasing power and the tendency to demonstrate higher social status through marriage can lead to an increase in the amount of dowry. Religious influence also plays an important role in determining the amount of dowry. In the Islamic view, dowry is considered a right that must be given to the wife. Islamic teachings also emphasize the importance of dowry as a condition for the validity of a marriage. Cultural changes also have an impact on changes in the amount of dowry in Indonesian wedding traditions. In Indonesian legislation, the issue of dowry is regulated in the Compilation of Islamic Law (KHI) in the chapter that regulates dowry. This law provides guidelines regarding the determination and delivery of dowry in marriage. Thus, it can be concluded that changes in the amount of dowry in wedding traditions in Indonesia are influenced by social, economic, religious and cultural factors. The existence of social and economic developments, the influence of religion in Islamic views, and changes in societal culture have a significant impact in determining the amount of dowry given at marriages in Indonesia.Keywords: Dowry, Tradition, Wedding, Trends. Abstrak : Dalam analisis perubahan dan tren jumlah mahar dalam tradisi pernikahan di Indonesia, dapat disimpulkan bahwa terdapat beberapa faktor yang mempengaruhi perubahan tersebut. Pertumbuhan sosial, ekonomi, budaya, dan pengaruh agama memiliki peran signifikan dalam menentukan jumlah mahar yang diberikan dalam pernikahan. Peningkatan daya beli masyarakat dan kecenderungan untuk menunjukkan status sosial yang lebih tinggi melalui pernikahan dapat menyebabkan peningkatan jumlah mahar. Pengaruh agama juga berperan penting dalam penentuan jumlah mahar. Dalam pandangan Islam, mahar dianggap sebagai hak yang wajib diberikan kepada istri. Ajaran agama Islam juga menekankan pentingnya mahar sebagai syarat sahnya pernikahan. Perubahan budaya juga berdampak pada perubahan jumlah mahar dalam tradisi pernikahan di Indonesia. Dalam perundang-undangan Indonesia, masalah mahar diatur dalam Kompilasi Hukum Islam (KHI) pada bab yang mengatur tentang mahar. Undang-undang ini memberikan pedoman mengenai penentuan dan penyerahan mahar dalam pernikahan. Dengan demikian dapat disimpulkan bahwa perubahan jumlah mahar dalam tradisi pernikahan di Indonesia dipengaruhi oleh faktor sosial, ekonomi, agama, dan budaya. Adanya perkembangan sosial dan ekonomi, pengaruh agama dalam pandangan Islam, serta perubahan budaya masyarakat memiliki dampak yang signifikan dalam menentukan jumlah mahar yang diberikan dalam pernikahan di Indonesia.Kata kunci : Mahar, Tradisi, Pernikahan, Tren.